School improvement needs analysis of the public primary schools in Istanbul - Dag, Sukran; Gumuseli, Ali Ilker (ELSEVIER SCIENCE BV, 2011)
The aim of this study is to analyze the school improvement needs of the public primary schools in Istanbul by considering the basic elements of school improvement and using these elements as the criteria of the school improvement needs analysis. According to the research results related with the first problem, it can be said that the school improvement needs of the schools are not so different in the subject of features of effective schools with respect to perceptions of the teachers working at the primary schools in Istanbul. (C) 2011 Published by Elsevier Ltd.
Keywords: School improvement; needs analysis; educational administration; education; Education & Educational Research